2013
DOI: 10.1073/pnas.1314415110
|View full text |Cite
|
Sign up to set email alerts
|

QsIA disrupts LasR dimerization in antiactivation of bacterial quorum sensing

Abstract: Significance Quorum sensing is a bacterial cell–cell communication system that is activated when the concentration of quorum sensing signal (autoinducer) reaches a threshold. In Pseudomonas aeruginosa , an opportunistic human pathogen, the quorum sensing threshold and response are defined by a novel antiactivator, QslA, which binds to the transcription factor LasR and prevents it from binding to its target DNA. However, how QslA binds to LasR and negatively regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 48 publications
0
43
0
Order By: Relevance
“…TraM binds the DNAbinding domain of TraR on the opposite side of the DNAbinding surface (46,47). More recently, structural characterization of the LasR-binding antiactivator QslA of Pseudomonas aeruginosa (48) revealed that in contrast to TraM, QslA binds the ligand-binding domain of LasR (48). Thus, antiactivators of LuxR-family regulators have evolved multiple times and can operate through distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…TraM binds the DNAbinding domain of TraR on the opposite side of the DNAbinding surface (46,47). More recently, structural characterization of the LasR-binding antiactivator QslA of Pseudomonas aeruginosa (48) revealed that in contrast to TraM, QslA binds the ligand-binding domain of LasR (48). Thus, antiactivators of LuxR-family regulators have evolved multiple times and can operate through distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…A third protein, QslA (PA1244), acts as a potent anti-activator of LasR through heterotrimer formation that can even dissociate previously formed LasR-DNA complexes (Seet and Zhang, 2011 ). This effect is achieved through direct binding of QslA to the ligand-binding-domain (LBD) of LasR in a 2:1 ratio, obscuring the dimerization interface and thereby preventing activation (Fan et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Gupta and Schuster found that mutations in either qteE or qscR can produce virtually identical phenotypes under certain conditions (Gupta and Schuster, 2013 ). QteE, QscR, and QslA are not homologous and may bind R-proteins differently (Siehnel et al, 2010 ; Lintz et al, 2011 ; Fan et al, 2013 ). In consideration of this evidence together, several important open questions remain.…”
Section: Introductionmentioning
confidence: 99%
“…35 Even when bound to its native AHL signal ( N -(3-oxo)-dodecanoyl L-homoserine lactone, OdDHL; Figure 1), only structures of the truncated N-terminal ligand-binding domain LasR have been solved to date. 3537 Further, there have been only two reported studies of LuxR-type proteins bound to non-native ligands: first, the LasR N-terminal domain bound to triphenyl (TP)-type synthetic activators, 35, 38 and second, full-length CviR (from Chromobacterium violaceum ) bound to three AHLs exhibiting differing degrees of partial agonism (octanoyl L-homoserine lactone, decanoyl L-homoserine lactone, and the “chlorolactone” inhibitor CL). 39 …”
Section: Introductionmentioning
confidence: 99%